STUDENTSâ SELF ESTEEM IN SPEAKING ABILITY - MR, Elvira Rosyida (JURNAL SMART, 2016)
One of principle of communicative competence is the students know how to uselanguage according to the setting and the participants. Actually, to be able to speaktarget language, the students ar not only expected to have a great ability in grammar,vocabulary, or writing, but how brave they express their idea and use target languageto others. Therefore, this study aimed to investigate studentsâ self esteem to theirspeaking ability This study was carried out at Hadist major at the fourth semester ofIAIN Raden Intan Lampung. The researcher used questionnaire, test, and interview.The data collected were analyzed quantitatively, and described to know clearly theprocess which was occurred during the research. The results indicate that studentsâself esteem influence their speaking ability.Key Words: speaking, self esteem, communicative competence